-6(-4n+2)-n=12n+4(-12+2n)

Simple and best practice solution for -6(-4n+2)-n=12n+4(-12+2n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-4n+2)-n=12n+4(-12+2n) equation:



-6(-4n+2)-n=12n+4(-12+2n)
We move all terms to the left:
-6(-4n+2)-n-(12n+4(-12+2n))=0
We add all the numbers together, and all the variables
-6(-4n+2)-n-(12n+4(2n-12))=0
We add all the numbers together, and all the variables
-1n-6(-4n+2)-(12n+4(2n-12))=0
We multiply parentheses
-1n+24n-(12n+4(2n-12))-12=0
We calculate terms in parentheses: -(12n+4(2n-12)), so:
12n+4(2n-12)
We multiply parentheses
12n+8n-48
We add all the numbers together, and all the variables
20n-48
Back to the equation:
-(20n-48)
We add all the numbers together, and all the variables
23n-(20n-48)-12=0
We get rid of parentheses
23n-20n+48-12=0
We add all the numbers together, and all the variables
3n+36=0
We move all terms containing n to the left, all other terms to the right
3n=-36
n=-36/3
n=-12

See similar equations:

| 2100=3400x+600 | | -2(7-6y)+4=-4 | | 20-4r=-4(1×4r) | | -9(-2k+10)=9(k+11) | | 3/5(x+4)=6 | | -2×-3=-(4x-15) | | 3x+2(x+6)=10 | | -(7-2x)=-7 | | 2(-3x-1)=6x+22 | | 0.4x+0.7=0.8x-1.3 | | 3x+5-6=6x+4 | | 0.4x+0.7=0.8x-1.4 | | -p+p=6(1-3p)-7(-7p-8) | | 2/3y-2/3=5 | | 2/3y-3/5=5 | | 23-k=13 | | 18y-12=2(9y-6) | | 8x+4(4x-3)=24+12 | | -2/3x+6=0 | | -5(1-6x)=8x-5(1+10x) | | 2x-4x-15=-2x+4-15 | | 36+x=76 | | -2x+7(3x-1=31 | | 2/y-2/5=1/y+11/10 | | 2m-9=m-5 | | 12+12(-4v+4)=10(6-7v)-9v | | 6a+a^2=8 | | -25-27v=25+7v | | 1/8-5/7(x-5/32)=4x/9+1/12 | | X+4/5=x/10 | | (5-y)+(-y)-(5-y)=0 | | 446=7n+6(1+8n) |

Equations solver categories